Motivaciones del turista de tercera edad en la selección de destinos turísticos - Carranza Juanazo, Adonis Emanuel (2023)
The main purpose of this study case is found in the exhaustive analysis of the motivation that senior tourists have to select tourist destinations. To achieve this goal, an exploratory research was applied with a quantitative approach. The technique was the survey which was applied to a representative group of individuals belonging to the “Asociación de Jubilados, Pensionistas y Anexos” of Babahoyo. Through the application of a questionnaire specially designed for this purpose. This methodological approach made possible to obtain quantitative data on the motivation and preferences of elderly tourists in their process of selecting tourist destinations